Bifunctional regulators of photoperiodic flowering in short day plant rice - Sun, Changhui; He, Changcai; Zhong, Chao; Liu, Shihang; Liu, Hongying; Luo, Xu; Li, Jun; Zhang, Yuxiu; Guo, Yuting; Yang, Bin; Wang, Pingrong; Deng, Xiaojian (Frontiers in Plant Science, 2022)
Photoperiod is acknowledged as a crucial environmental factor for plant flowering. According to different responses to photoperiod, plants were divided into short-day plants (SDPs), long-day plants (LDPs), and day-neutral plants (DNPs). The day length measurement system of SDPs is different from LDPs. Many SDPs, such as rice, have a critical threshold for day length (CDL) and can even detect changes of 15 minutes for flowering decisions. Over the last 20 years, molecular mechanisms of flowering time in SDP rice and LDP Arabidopsis have gradually clarified¸which offers a chance to elucidate the differences in day length measurement between the two types of plants. In Arabidopsis, CO is a pivotal hub in integrating numerous internal and external signals for inducing photoperiodic flowering. By contrast, Hd1 in rice, the homolog of CO, promotes and prevents flowering under SD and LD, respectively. Subsequently, numerous dual function regulators, such as phytochromes, Ghd7, DHT8, OsPRR37, OsGI, OsLHY, and OsELF3, were gradually identified. This review assesses the relationship among these regulators and a proposed regulatory framework for the reversible mechanism, which will deepen our understanding of the CDL regulation mechanism and the negative response to photoperiod between SDPs and LDPs.